Mobile game 3D - Ho, Huu Huy. (2010)
The market for mobile games and applications, especially 3D games, is potentially huge and growing quite fast recently. Mobile technology has enabled developers to create games which not only perform well but also have amazing graphics capabilities. Although rhythm games, among which Audition is arguably the most popular, abound in the market, I found no rhythm game in 3D available for mobile phones at present. The primary purpose of my final year project is thus to design and develop a game of this kind.